2013
DOI: 10.2217/pgs.13.146
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF- α Polymorphism with Prediction of Response to TNF Blockers in Spondyloarthritis and Inflammatory Bowel Disease: A Meta-Analysis

Abstract: Individuals with the TNF-α-308 G allele and -857 C allele showed better anti-TNF-α treatment responses than those with the TNF-α-308 A allele and -857 T allele. The -308 G/G genotype and -857 C/C genotype are predictors of good response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 32 publications
2
15
0
1
Order By: Relevance
“…Previous studies found that the expression of TNF-α is higher in patients carrying the -308A allele than in those carrying the -308G allele, suggesting that this polymorphism has functional implications in inflammation and may be associated with inflammatory diseases [ 10 ]. In fact, previous studies have demonstrated the association of this polymorphism with certain inflammatory diseases, such as fatty liver disease [ 11 ], hepatitis B virus infection [ 12 ], systemic lupus erythematosus [ 13 ], inflammatory bowel disease [ 14 ], arteritis [ 15 ] and rheumatoid arthritis [ 16 ]. Several case–control studies have been conducted to clarify the association between the TNF-α -G308A polymorphism and risk of OA [ 17 23 ]; however, the results are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that the expression of TNF-α is higher in patients carrying the -308A allele than in those carrying the -308G allele, suggesting that this polymorphism has functional implications in inflammation and may be associated with inflammatory diseases [ 10 ]. In fact, previous studies have demonstrated the association of this polymorphism with certain inflammatory diseases, such as fatty liver disease [ 11 ], hepatitis B virus infection [ 12 ], systemic lupus erythematosus [ 13 ], inflammatory bowel disease [ 14 ], arteritis [ 15 ] and rheumatoid arthritis [ 16 ]. Several case–control studies have been conducted to clarify the association between the TNF-α -G308A polymorphism and risk of OA [ 17 23 ]; however, the results are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…In China, anti-TNF-α therapy is widely applied as treatment for various rheumatic diseases due to its clinical efficacy [ 15 16 ]. However, since their clinical availability in 2006, studies have reported adverse events inconsistent with original drug-safety profiles [ 17 ], and showed anti-TNF-α treatment can result in serious adverse events [ 18 – 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several important differences between the present study and two related meta-analyses that had been published previously3536. In the present study, we included more patients than either of the two previous studies and added a set of unpublished data from our lab.…”
Section: Discussionmentioning
confidence: 95%